ANALYSIS OF INCREASED C-REACTIVE PROTEIN LEVELS IN BLOOD SERUM OF RATTUS NORVEGICUS WISTAR STRAIN DUE TO INTAKE OF POLYETHYLENE MICROPLASTICS - Julian, Alvin; Suwasanti, Niluh; Sincihu, Yudhiakuari; Novita, Bernadette Dian; Samsudin, Kevin (JOURNAL OF WIDYA MEDIKA JUNIOR, 2024)
Background: The widespread use of plastic and poor management of plastic waste is an environmental problem and has an impact on human health. The most commonly found microplastic contaminant is polyethylene polymer. Ingested microplastic particles will undergo an endocytosis mechanism and be absorbed into the bloodstream. This then triggers an increase in reactive oxygen species (ROS) which induces oxidative stress and results in an inflammatory response. This study tries to analyze the effect of administering microplastics on increasing blood serum C-reactive protein as a biomarker and marker of the inflammatory response due to microplastics. Method: The experimental analytical research used 42 Rattus Norvegicus Wistar Strain animals, which were divided into 5 experimental groups and 1 control group. Quantitative data measurements/collection were carried out at two times (pre-post-test control group design) and analyzed by non-parametric comparison using the Friedman Test to see the increase in C-Reactive Protein (CRP) levels in the blood serum of Rattus norvegicus Wistar Strain before and after being given intake polyethylene microplastics. Result: In all groups X0-X5, The results of the comparative test using the Friedman test showed a significant value of P = 0.000 (P < 0.05), so it can be concluded that there is a difference in pre and post experimental CRP levels. Discussion: The increase in serum CRP levels from the control group to the X5 treatment group may be due to oxidative stress mechanisms, especially in hepatocyte cells, smooth muscle cells, macrophage cells, endothelial cells, lymphocyte cells and adipocyte cells which induce the production of CRP protein, especially native C-reactive protein (nCRP) and monomeric C-reactive protein (mCRP). The difference in serum CRP levels was significant (P = 0.000), where there was an increase in serum CRP levels post treatment (post experimental) from the lowest mean of 0.05 mg/L (pre experimental) to the highest of 0.98 mg/L on average, indicating that administration of microplastic intake at the dose studied had an impact on increasing serum CRP levels in response to an inflammatory reaction. The limitation of this research is that there are no journals that examine microplastics on serum CRP levels, resulting in a lack of research that can be used as a reference or comparative theory. Conclusion: Administration of Microplastic Polyethylene at the dose studied in the treatment group caused a significant increase in Rattus Norvegicus Wistar Strain Serum CRP levels.